Beach processes and sedimentation - Komar, Paul D., 1939- (Upper Saddle River, N.J. : Prentice Hall, 1998)
An introduction to the study of beaches. The geomorphology of eroding and accreting coasts. Beach morphology and sediments. The changing level of the sea. The generation of waves and their movement across the sea. Wave breaking and surf-zone processes. Beach profiles and cross-shore sediment transport...
Keywords: Coast changes; Beach processes; Coast changes; Marine sediments; Ocean waves; Tides